Bacteria Isolated From Respiratory Tract and Abscesses in Livestock: Bakteri yang Diisolasi dari Saluran Pernafasan dan Abses pada Ternak - Dawoud, Salma Abd Al-Hussein; Abbas , Ismail Juma (Indonesian Journal on Health Science and Medicine, 2025)
This research aims to identify the types of bacteria that have been isolated from various body fluids, including the abscess secretions and nasal secretions of sheep and cows. Cotton swabs were used togather isolates from animals suffering from respiratory ailments and abscesses. The specimens were subsequently transferred to the microbiological laboratory. They were cultured on blood agar media and incubated for a duration of 24 to 48 hours at a temperature of 37°C. Following the purification of the samples, traditional diagnostic methods, including biochemical tests, were conducted. Polymerase chain reaction, Its foundation is the utilization of the 16SrRNA gene which depends genetic material to diagnose bacteria .The 16SrRNA gene, found in all bacterial species, contains nine heterogeneous regions that facilitate the identification of various types of bacteria.. The sequence of the samples is then compared with the sequence found in GenBank, each bacteria has an international number by which it can be identified. The results of isolates obtained from the nasal secretions is Acinetobacter baumannii and from abscess secretions is Staphylococcus agnetis The study revealed that rare specimens were obtained and registered in the gene bank bearing the following numbers , PP809047.1 , PP809049.1. The results of the study also confirmed that some isolates, especially bacteria, are pathogenic and pose a danger to animals, but when transmitted to humans, they are deadly due to their opportunistic nature. Highlights: Bacteria isolated from sheep and cow secretions: Acinetobacter baumannii, Staphylococcus agnetis. Diagnostic methods: blood agar, biochemical tests, PCR using 16SrRNA gene. Rare specimens registered in GenBank, potentially pathogenic to animals and humans. Keywords: Respiratory tract infection , Body fluids ,Livestock.